The American steel industry 1850-1970: - Warren, Kenneth (Clarendon, 1973)
In this empirically based study, United States present a current, comprehensive, and in-depth view of U.S heavy industry capacity and suggest that significant changes in production locations and manufacturing efficiency levels are warranted.